Deixis in the Song Lyrics of Lewis Capaldi’s “Breach” Album - Dayana Sinaga; Herman Herman; Tiarma Intan Marpaung (Journal of Languages and Language Teaching, 2020)
The aim of the research is to analyze the three types of deixis analysis using Yule’s (1996) theory and interpret the reference meaning of deixis that are found in the Lewis Capaldi’s “Breach” album song lyrics. The researchers selected this song as subject of analysis because the popularity of the song and also it consisted of such as deictic words. Therefore, the “Breach” album song lyrics can be analyzed by using pragmatic approach especially using theory of Yule (1996) about deixis analysis. This study was conducted by using descriptive qualitative method. The kind of this research is content analysis. The data which used song lyrics of Lewis Capaldi’s “Breach” album (2018). In addition, this song was classified into three types of deixis analysis based on their own criteria. The result of this research showed that the three types of deixis using Yule’s theory such as person deixis, spatial deixis and temporal deixis are used in the Lewis Capaldi’s “Breach” album. The most dominant type of deixis in this research were found is person deixis with 11 data (55%), spatial deixis with 6 data (30%), and temporal deixis with 3 data (15%). The use of person deixis indicated the participant in this song. While, the spatial deixis indicated location and place of event from the participant. Moreover, the temporal deixis indicated the timing of speech event which is used in this song.